Empowering Learning: The Evolution of the Independent Learning Curriculum in the Era of Technology - Afiful Ihwan; Ahmad Barizi; Wahidmurni Wahidmurni (AL-ISHLAH: Jurnal Pendidikan, 2026)
This study aims to critically analyze the evolution and implementation of the Independent Learning Curriculum in Indonesia within the context of rapid technological development. The focus is placed on examining how curriculum autonomy, pedagogical competence, and digital integration interact in shaping contemporary learning practices. This research employs a qualitative library research method by systematically reviewing 32 scholarly sources, including peer-reviewed journal articles and academic books published between 2019 and 2024. The data were analyzed using thematic and comparative analysis, guided by constructivist learning theory, curriculum innovation theory, and digital pedagogy as the main analytical frameworks. The findings reveal that the Independent Learning Curriculum represents a significant shift toward learner-centered and flexible education, emphasizing autonomy, character development, and the use of digital technology to expand learning opportunities beyond the classroom. However, the analysis also indicates persistent challenges, particularly disparities in digital infrastructure, uneven teacher readiness, and inconsistencies in policy implementation across educational contexts. These factors limit the transformative potential of curriculum innovation when not supported by adequate institutional capacity and professional development. The study concludes that the successful implementation of independent learning in the digital era requires systemic alignment between pedagogical innovation, technological accessibility, and institutional readiness. By synthesizing existing literature, this article proposes a conceptual framework that integrates learner autonomy, digital facilitation, and teacher capacity building as key components of sustainable curriculum reform. This framework offers practical insights for policymakers and educators in strengthening the effectiveness and equity of independent learning implementation in diverse educational settings.